The practice of IFSB guiding principles of risk management by Islamic banks International evidence - Rosman, R; Rahman, ARA (Emerald Group Publishing Ltd, 2024)
Purpose - The purpose of this study is to examine the nature of the risk management practices of Islamic banks as recommended by the Islamic Financial Services Board (IFSB) in managing their unique risks. This study also explores the differences in risk management practices based on the country, size, type and age of the bank. Design/methodology/approach - A questionnaire was developed to investigate the risk management practices. The main reference for the questionnaire was the IFSB Guiding Principles of Risk Management and the respondents were either the chief risk officers or holders of other senior positions involved in risk management in the Islamic banks. A non-parametric test was then conducted to explain the difference in mean scores for the unique risk management practices by the Islamic banks. Findings - A lack of effective risk management practices was found in relation to liquidity risk, displaced commercial risk and equity investment risk by Islamic banks. However, Islamic banks were comparatively good in managing operational risk/Shari'ah non-compliance risk. The study found that there was a significant difference in the practice of equity investment risk management based on the size, type and age of the Islamic bank. In addition, a significant difference was found between the Islamic banks in the Middle Eastern and North African (MENA) and Asian countries concerning the practice of both displaced commercial risk and operational risk/Shari'ah non-compliance risk management. Research limitations/implications - In spite of the limitations in non-parametric analysis, this analysis was preferred inasmuch as the data were measured on an ordinal scale with a small sample size. Originality/value - This study is among the few studies that examine and explore the risk management practices of Islamic banks internationally by explaining the unique risks encountered in Islamic finance.